Perbandingan Kegiatan Pembelajaran Konvensional dan Pembelajaran Berbasis Teknologi Terhadap Hasil Belajar Siswa (Studi Kasus pada Kls VIII A SMP Cerdas Bangsa, Kecamatan Namorambe Kabupaten Deli Serdang) - Suci Dahlya Narpila; Dinda Dyah Pitaloka; Rizky Ramadhan; Abdul Muttaqin Rusydi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study examines the comparison between conventional learning and technology-based learning on student learning outcomes. The purpose of this study is to understand the meaning of the comparison between the two learning methods, explore the meaning of conventional learning, technology-based learning, and student learning outcomes, and finally compare the effectiveness of the two methods in improving the learning outcomes of grade VIII students at SMP Cerdas Bangsa. The methods used in this study are literature studies and experiments involving two groups of students; the first group follows conventional learning, while the second group follows technology-based learning. The results of the study indicate that technology-based learning has a more significant impact on improving student learning outcomes compared to conventional learning.